Panniculitis in reactivation of Chagas disease in a cardiac transplant patient - Gabriela T. Batiston; Gabriella B. Pintos; João R. Antonio; Eduardo C.N. Constantino; Daniel Villafanha (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Reactivation of chronic Chagas disease is a rare condition, occurring solely in immunosuppressed patients. Skin involvement has been reported in patients with chronic Chagas disease and heart or kidney transplantation who reactivated the trypanosomiasis. In all cases involving the skin, amastigote forms of Trypanosoma cruzi are detected. Our case focuses on a 51-yearold female with a history of cardiac transplantation due to Chagas disease and immunodepression. The dermatology team was consulted due to the presence of painful erythematous nodules, after 30 days of hospitalization. Initially, a skin biopsy suggested cutaneous leishmaniasis as a hypothesis. However, subsequent immunohistochemistry confirmed the presence of T. cruzi, leading to the decision to treat for Chagas disease reactivation. The development of panniculitis is not commonly associated with Chagas disease. This case underscores the importance of not disregarding such possibilities and highlights the necessity for histopathological and immunohistochemical analyses to complement the diagnostic process.